Specificity and Components of Successful Educational Work of a Curator with First-Year Students - Bilousova, Ludmila; Olkhovsky, Eugene (Pedagogical Discourse, 2012)
The article is devoted to coverage of the factors that cause the specificity of curator’s work with first-year students and it determines tasks of such work. The practice-oriented ways of success achievement in this work are outlined